ANALYSIS OF USER PERCEPTION OF THE COMFORT LEVEL OF PEDESTRIAN PATH IN THE TRADITIONAL MARKET AREA OF KADIPATEN, MAJALENGKA - Angga Pratama; Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2024)
Pedestrian facilities are a means of transportation to facilitate and provide comfort for outdoor activities. Currently, the Majalengka Regency Government Public Works and Spatial Planning Office of Majalengka Regency continues to improve the development sector, namely the improvement of pedestrian paths in several areas, one of which is the construction of pedestrian paths in the Kadipaten Traditional Market Area. Everyday path is always crowded with visitors, not only buying and selling activities in the market, but some want to enjoy the scenery. It makes the pedestrian path a very dense zone and becomes for comfort in activities in public spaces. The study aims to determine the influence of conditions in the pedestrian area on the felt. The methods used are qualitative and quantitative, by conducting physical observations and then validating the findings of physical observation with opinions from users obtained from the results of the distribution of 100 questionnaires about the conditions of the pedestrian path that affect the comfort of user perception. the study concluded that 100 samples of road user respondents stated that the condition of the pedestrian path obtained a good predicate with a score of 2.59 (scale 4). The highest score was the safety factor score from the pedestrian condition. Final results showed that 73% of respondents stated that the pedestrian path in the Kadipaten Traditional Paasar Area had fulfilled comfort.